Community Benefits or Community Bribes? An Experimental Analysis of Strategies for Managing Community Perceptions of Bribery Surrounding the Siting of Renewable Energy Projects. (January 2017) - Walker, Benjamin J.A.; Russel, Duncan; Kurz, Tim
The provision of financial incentives to local communities by energy developers has attracted cynicism across many localities, with some suggesting such community benefits are akin to "bribery." The current study used an experimental design embedded within a community postal survey to explore whether potentially damaging effects of bribery rhetoric upon local support for a wind farm can be overcome through (a) portraying community benefits as a policy requirement (rather than a discretionary gesture by developers), and/or (b) the deployment of different discursive strategies by developers to manage their stake in the outcome of the project. Participants told about community benefits as being a policy requirement showed significantly higher support for the wind farm, an effect that was mediated by heightened perceptions of individually and collectively favorable outcomes from the development. We discuss our results in relation to their implications for government policy approaches to promoting renewable energy supply.